Prospectiva Estratégica para el Centro Comercial Cruz Azul, Hidalgo. México (2019)
In the present article a strategic prospective study is developed to propose to the General Management of the Cruz Azul Shopping Center, the making of the best decisions that support the growth of the company. Likewise, the prospective concepts of different authors have been considered, reflecting that the growth of the companies is large or small, they will have to be based on an analysis of the situation in which they are, and where they want to go, taking into account components such as uncertainty, competition, globalization, consumer culture, technology and social trends. In this beginning of analysis the tool of study of the situation of the company is used, analyzing its internal characteristics (Weaknesses and Strengths) and its external situation (Threats and Opportunities) (SWOT). Thus, through the strategic prospective is that you can improve the current situation of this shopping center, so that the medium and long-term plans is to achieve market position as one of the best shopping options within from the Tula Tepeji region.